2018
DOI: 10.1364/boe.9.004539
|View full text |Cite
|
Sign up to set email alerts
|

Muscular blood flow responses as an early predictor of the severity of diabetic neuropathy at a later stage in streptozotocin-induced type I diabetic rats: a diffuse correlation spectroscopy study

Abstract: We propose a novel application of diffuse correlation spectroscopy to evaluate microvascular malfunctions of muscle tissue affected by hyperglycemia and determine their correlation with the severity of diabetic neuropathy at a later stage. Microvascular responses of the thigh muscle and the mechanical pain threshold of the hind paw of streptozotocin-induced type I diabetic rats were continuously monitored once per week for 70 days. Significantly decreased baseline blood flow and reactive hyperemia responses we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…It has been reported that microvascular malfunctions of muscle tissue are affected by hyperglycemia and are correlated with the severity of diabetic neuropathy in later stages. 80 With the development of HRU, muscle atrophy (resulting from a variety of factors) can be identified at an earlier stage. The lack of research on the normal value of muscle observed by ultrasound and the diagnostic value of muscle in patients with DA necessitates further study using HRU of the characteristics of various neurologic diseases.…”
Section: Diagnosis Of Diabetic Muscular Atrophymentioning
confidence: 99%
“…It has been reported that microvascular malfunctions of muscle tissue are affected by hyperglycemia and are correlated with the severity of diabetic neuropathy in later stages. 80 With the development of HRU, muscle atrophy (resulting from a variety of factors) can be identified at an earlier stage. The lack of research on the normal value of muscle observed by ultrasound and the diagnostic value of muscle in patients with DA necessitates further study using HRU of the characteristics of various neurologic diseases.…”
Section: Diagnosis Of Diabetic Muscular Atrophymentioning
confidence: 99%
“…In future work, we intend to compare the results between diabetic patients and healthy subjects to assess the key factors distinguishing these two groups, so that early diagnosis of diabetic complications may be possible. To date, some research groups have studied the early diagnosis of diabetic complications using optical systems with near-infrared sources 44 46 . However, these studies have focused on the time-averaged hemodynamic variables and disregarded LFO information.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed description of the DCS system is provided elsewhere (Nakabayashi and Ono ; Ono et al. ). Briefly, the system consists of a long coherence, continuous wave laser operating at 785 nm (DL 785‐100‐S, 100 mW; CrystaLaser, USA), which serves as the source, and a photon‐counting avalanche‐photodiode, which serves as the detector (COUNT‐T‐100‐FC; Laser Components, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…; Frisbee ; Ono et al. ). Elevated adrenergic vascular tone is one of the factors that compromises the capacity for vasodilation in such pathological states as diabetes mellitus and metabolic syndrome (Friedman ; Frisbee , ; Ono et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation